Clinical features, risk factors, diagnosis, and treatment of trimethoprim-sulfamethoxazole-induced hypoglycemia - Wang, Chunjiang; Fang, Weijin; Li, Zuojun; Sun, Linli (Frontiers in Endocrinology, 2023)
Objective: Hypoglycemia is an extremely rare and serious adverse reaction of trimethoprim-sulfamethoxazole (TMP-SMX) due to its sulfonylurea-like effect. We explored the clinical features, risk factors, treatment, and prognosis of TMP-SMX-induced hypoglycemia. Methods: We systematically searched case reports and case series of TMP-SMX-induced hypoglycemia using Chinese and English databases, and extracted basic patient information and clinical information for analysis. Results: A total of 34 patients were enrolled from 31 literatures (16 males and 18 females). Patients had a median age of 64 years (range 0.4-91), commonly had renal dysfunction (75.8%). The median duration of a hypoglycemic episode was 6 days (range 1-20), and the median minimum glucose was 28.8 mg/dL (range, 12-60). Thirty-two patients (97.0%) showed neuroglycopenic symptoms, with consciousness disturbance (30.3%) and seizure (24.2%), sweating (18.2%), confusion (15.2%), asthenia (12.1%) being the most common symptoms. Fifteen patients (44.1%) had elevated serum insulin levels, with a median of 31.8μU/mL (range 3-115.3). C-peptide water increased in 13 patients (38.2%), with a median of 7.7 ng/mL (range 2.2-20). Complete recovery of symptoms occurred in 88.2% of patients without sequelae. The duration of hypoglycemia symptoms was 8h-47d after intervention including discontinuation of TMP-SMX, intravenous glucose, glucagon, and octreotide. Conclusion: Hypoglycemia is a rare and serious adverse effect of TMP-SMX. Physicians should be alert to this potential adverse effect, especially in patients with renal insufficiency, increased doses, and malnutrition.